2004
DOI: 10.1007/s00464-004-8811-3
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative fluid management in laparoscopic live-donor nephrectomy: Challenging the dogma

Abstract: Lower volume fluid management strategies in LLDN do not appear to worsen recipient outcomes nor are they detrimental to the donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…However, the delayed graft function was 18% in the restrictive fluid group v 10% in the liberal fluid group. 36 In the present study, more fluid was administered intraoperatively (13 mL/kg/h crystalloids and 12 mL/kg colloids in total), but delayed graft function occurred in only 2% after LDN.…”
Section: Discussionmentioning
confidence: 85%
“…However, the delayed graft function was 18% in the restrictive fluid group v 10% in the liberal fluid group. 36 In the present study, more fluid was administered intraoperatively (13 mL/kg/h crystalloids and 12 mL/kg colloids in total), but delayed graft function occurred in only 2% after LDN.…”
Section: Discussionmentioning
confidence: 85%
“…8,26,27 Furthermore, no significant differences were observed in recipient postoperative complications, graft loss, and death among fluid management groups. These terms were decided after consultation and data interpretation with our expert anesthesiology colleagues.…”
Section: Discussionmentioning
confidence: 89%
“…4 Despite the safety and benefits of LDN, there is no consensus regarding the intraoperative fluid management required to optimize donor and recipient outcomes. 4,8,9 In addition, much of the literature is outdated and based on animal models. 4,8,9 In addition, much of the literature is outdated and based on animal models.…”
mentioning
confidence: 99%
“…4 This raises the question of how beneficial and necessary fluid replacement and confirmation of a brisk diuresis from the transected ureter is during laparoscopic donor nephrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Bergman and colleagues 4 reported that renal donors receiving fluid-load (>10mL/kg/hr) and fluid-restriction (<10mL/kg/hr) did equally well in terms of postoperative creatinine levels and complications. Furthermore, there were no differences in recipient postoperative creatinine levels (to 12 months), delayed graft function, or acute rejection.…”
Section: Introductionmentioning
confidence: 99%